(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Preeclampsia is a form of high blood pressure manifested during pregnancy; however, its etiology is unknown. Also, the status of ionized calcium (Cai) during pregnancy and its complication preeclampsia have not been described adequately. In addition to calculation method described for Cai, the calcium-binding dye murexide has become a widely-used tool for measuring changes in the ionized calcium (Cai) concentration in biological systems. Objective:to demonstrate the level of Cai during preeclampsia with respect to normal pregnancy; and to demonstrate the correlation between calculated Cai and actual Cai. Subject and methods: the present study is a case-control study conducted during the period from February 2007 until the end of June 2007, which includes measurement of total, corrected and ionized calcium (Cai) in 60 patients with preeclampsia that are classified according to gestational age into preeclamptics in the second trimester G1 (n=30) and preeclamptics in the third trimester G2 (n=30). The results are compared with 60 apparently healthy pregnants controls that are classified according to gestational age into two groups G3 (n=30) and G4 (n=30). Results: the serum corrected total calcium; serum calculated ionized Cai and actual Cai are significantly reduced in preeclamptics in the third trimester (G1) compared with normal pregnants (G4) (P